THE COST OF MULTITASKING: A COMPUTER-ASSISTED QUANTITATIVE STUDY OF TASK-SWITCHING COSTS IN SPEED AND ACCURACY BY AGE AND GENDER - Lou, Joseph D (PEOPLE: International Journal of Social Sciences, 2018)
Multitasking is known to have negative impacts on productivity. However, there has been no systematic study on its negative effects comparing age and gender groups at a large scale. Due to limitations in previous methods, this study aimed to develop an original web-based Multitasking Test (MTT) tool and then use it to test a large sample of diverse participants on their task-switching costs (time and accuracy lost when multitasking). MTT allowed participants (N = 1,004) to each conduct 6 pattern-matching tasks with playing cards (20 trials per task). Results indicated that (a) high schoolers took 95% more time and made 120% more errors when multitasking than when performing single tasks separately; (b) the 22-25 age group performed the best among all groups, consistent with previous neuroscience findings that the human brain does not reach maturity until 24 years old; and (c) there were significant gender differences (p < .001) in switching costs in time, potentially explained by gender differences in the structural connectome of human brains. This study presents an innovative, computer-assisted methodological design and demonstrates how multitasking has switching costs across all age and gender groups regardless of prior experiences and education level. In addition to presenting strong empirical data that support the Cognitive Load Theory, it also provides a reliable multitasking paradigm for further studies in cognitive science, developmental psychology, and neuroscience.